Measure the effectiveness of the Balanced Scorecard strategic performance management in public institutions of Jordan )An Empirical Study on the Social Security Corporation – Irbid( - ملكاوي, احمد فوزي (Journal of Economics and Administrative Sciences, 2018)
The goal of this research to identify a set of criteria that can be measured on the basis of which the effectiveness of the application of the Balanced Scorecard in the Jordanian Public Institutions in order to identify the basic requirements to ensure the application of balanced performance measures. The study population consisted of the staff of the Public Institution for Social Security - Irbid of directors of departments and heads of departments and administrative staff, was the use of a random sample of (50) an employee and the employee. The questionnaire was used as a tool to collect data, and as a result of subjecting these standards for the field test and the use of statistical analysis tools to the results of the study concluded that the most important of which there are a set of criteria which are available at public institutions will work to ensure the success of the application of balanced performance measures. Among these standards:  The support of senior management necessary prerequisite for the success of the application of balanced performance measures in public institutions. The four axes of the Balanced Scorecard appropriate for application in public institutions. The four axes of the Balanced Scorecard enough to run a balanced performance in public institutions.4. The non-financial hubs are more important than the financial perspectives in the evaluation process in public institutions